Financial literacy, financial behavior, self-efficacy and financial health among Malaysian households: the mediating role of money attitudes - Sabri, Mohamad Fazli; Wijekoon, Rusitha; Abd Rahim, Husniyah; Burhan, Nik Ahmad Sufian; Madon, Zainal; Hamsan, Hanina Halimatusaadiah (Human Resource Management Academic Research Society, 2022)
Financial health is defined as the ability to manage spending, plan for and recover from financial shocks, have minimum debt, and develop wealth; however, the antecedents to this vital idea are inconsistent. As a result, the study’s main goal is to reveal the antecedents, and their direct and indirect consequences on people’s financial health. Malaysian households were chosen using the multi-stage random sampling procedure, and a questionnaire survey was conducted. According to PLS-SEM analyses, only financial behavior, and money attitudes had a direct influence on financial health, and accounted for 46.7% of the total variance in financial health. Surprisingly, all three antecedents had a favorable impact on individual financial health through their money attitudes. Furthermore, all three antecedents revealed substantial, and positive correlations with money attitudes, explaining 45.6% of the overall variance. The current study contributed to filling research gaps on the factors that influence money attitudes, and financial health, guiding policymakers in their efforts to improve people’s financial health through effective policy implementations.